Metaphor in applied linguistics: four cognitive approaches - Steen, Gerard (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This article presents some considerations into metaphor in language and thought - 'the topic and title of the first conference of its kind in Brazil'. The paper focuses on the discussions presented in the round table, which were mostly directed to the empirical research on metaphor in Applied Linguistics. This integrative and restropective reflection on the papers presented will be conducted from the perspective of the debate into the relationship between metaphor in language and in thought. This central issue is at the core of my proposal for four different approaches to metaphor, absed on the interdependence between language and thought as system and as use: 10 metaphor in language as system; 2) metaphor in thought as system; 3) metaphor in language as use; 4) metaphor in thought as use. Is is within the framework of these categories that metaphors should be studied, with a certain degree of autonomy, so that their interdependence can be better understood.